Preconception care to improve pregnancy outcomes: clinical practice guidelines - Atrash, Hani (2020)
Introduction: There is scientific evidence that the health of women before pregnancy contributes to the maternal and infant outcomes of pregnancy. There is also scientific evidence that the health of women of reproductive age may be improved through the provision of Preconception Care (PCC). Preconception care includes interventions to assess, identify, address, and modify a woman’s health conditions and risks to ensure that these health conditions and risks do not negatively affect the outcome of her pregnancy. Many of the medical conditions, environmental exposures, personal behaviors, and psychosocial risks associated with negative pregnancy outcomes have been identified and there are recommendations for including these conditions in PCC services. Objective: Our purpose is to present a tool for clinical care providers involved in delivering PCC services. We try to answer the following questions: what do providers actually do when a woman of reproductive age arrives at their offices? What questions to ask? What examinations to conduct? What laboratory tests to perform? And, what education and counselling to offer? Methods: We reviewed published and un-published literature related to the scientific evidence for the effectiveness of PCC in improving pregnancy outcomes. We searched PubMed for published articles, and we searched the internet for unpublished reports prepared by international organizations such as the World Health Organization and reports from governmental agencies. We summarized the information and presented a comprehensive overview of actions that providers should take to address various risk behaviors, exposures and health conditions. Results: Several scientists, countries, and international organizations have proposed answers to the above questions. However, there has been no consistency and there is not a single publication that includes a comprehensive compilation of the proposed actions. We summarized the recommended actions that clinical care providers should take in addressing various health conditions, risk behaviors, and exposures. Conclusion: It is recommended that all providers screen all women for their intentions to become pregnant and to provide them with appropriate services. Women should be referred to specialized care when risk behaviors and medical conditions that go beyond the skills and abilities of the primary care provider are identified.